Nurses' perceived benefits of trauma nursing rounds (TNR) on clinical practice in an Australian emergency department: A mixed methods study. Issue 1 (February 2015) - Dalmaso, Kym; Weber, Sarah; Eley, Rob; Spencer, Lyndall; Cabilan, C.J.
Summary Background Trauma nursing rounds (TNR) are a unique type of bedside teaching round that facilitate discussion of individual trauma patient's condition and care, and provide a novel and innovative approach to nursing education in an informal setting. This study introduced TNR to the emergency department in an Australian metropolitan hospital. Methods Registered nurses, assistants-in-nursing, and nursing students participated in seven TNR over a 12-week period. The primary care nurse presented the trauma case utilising a modified handover tool. This was followed by discussion of the patient's condition and management among all those present including the patient. A participant questionnaire provided feedback from the nurses about TNR perceived benefits. A representative sample of participants was subsequently interviewed. Results Fifty-three participants attended the rounds, 47 responded to the questionnaire, and nine were interviewed. Participants were universally positive about the TNR structure and its potential impact on clinical practice. Interviewees indicated that TNR have the potential to enhance collegiality, and allow the patients and their families to be involved and informed in their care. Conclusions The introduction of TNR was successful. TNR provide the potential to improve assessment and care of trauma patients, promote collaborative learning, and promote patients' understanding and involvement in their care.